The Impact of Economic Parameter Uncertainty Growth on Regional Energy Demand Assessment - Olga Vasilyevna Mazurova; Elena Vasilyevna Galperova (Экономика региона, 2017)
The article deals with the forecasting studies based on the energy demand and prices in the region in terms of the complex interconnections between economy (and energy) and the growth of uncertainty of the future development of the country and territories. The authors propose a methodological approach, which combines the assessment of the price elasticity of energy demand with the optimization of energy and fuel regional supply. In this case, the price elasticity of demand is determined taking into account the comparison of cost-effectiveness of using different types of fuel and energy by different consumers. The originality of the proposed approach consists in simulating the behaviour of suppliers’ (energy companies) and large customers’ (power plants, boiler rooms, industry, transport, population) depending on energy price changes, the existing and new technologies, energy-saving activities and restrictions on fuel supplies. To take into account the uncertainty of future economic and energy conditions, some parameters such as prospective technical and economic parameters, price, technological parameters are set as the intervals of possible values with different probability levels. This approach allows making multivariate studies with different combinations of the expected conditions and receiving as a result the range of the projected values of studied indicators. The multivariate calculations show that the fuel demand has a nonlinear dependence on the consumer characteristics, pricing, projection horizon, and the nature of the future conditions uncertainty. The authors have shown that this effect can be significant and should be considered in the forecasts of the development of fuel and energy sector. The methodological approach and quantitative evaluation can be used to improve the economic and energy development strategies of the country and regions